2020
DOI: 10.1093/geronb/gbaa077
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Efficacy of Working Memory Training in Healthy Older Adults: A Systematic Review and Meta-Analysis of 22 Randomized Controlled Trials

Abstract: Objectives The long-lasting efficacy of working memory (WM) training has been a controversial and still ardently debated issue. In this meta-analysis, the authors explored the long-term effects of WM training in healthy older adults on WM subdomains and abilities outside the WM domain assessed in randomized controlled studies. Method A systematic literature search of PubMed, Web of Science, PsycINFO, Cochrane Library, ProQues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 79 publications
0
26
0
Order By: Relevance
“…Telomeres are the regions at the ends of the linear chromosomes and are composed of DNA and proteins (Hou et al, 2020 ). Telomeres become shorter as cells divide unless mechanisms are present to prevent attrition.…”
Section: How Human Brains Age: Intra-neural and Inter-neural Hallmark...mentioning
confidence: 99%
See 1 more Smart Citation
“…Telomeres are the regions at the ends of the linear chromosomes and are composed of DNA and proteins (Hou et al, 2020 ). Telomeres become shorter as cells divide unless mechanisms are present to prevent attrition.…”
Section: How Human Brains Age: Intra-neural and Inter-neural Hallmark...mentioning
confidence: 99%
“…For instance, a recent meta-analysis of 43 studies on commercial training programs among healthy older adults (including a large-scale study from our own lab that we consider state-of-the art; Buitenweg et al, 2019 ) concluded that there is currently insufficient empirical evidence to support that such training can improve memory, general cognition, or everyday functioning (Nguyen et al, 2021 ). As to the efficacy of working-memory training, a hot debate is still raging (Karbach and Verhaeghen, 2014 ; Sala et al, 2019 ; Hou et al, 2020 ). In general, although cognitive training (especially of specific skills) might stimulate the genesis of neurons, myelin, and synapses, future research will need to establish whether cognitive training in older adults incurs direct effects on (multiple) other hallmarks of normal neural aging.…”
Section: How Interventions Can Potentially Accelerate or Decelerate B...mentioning
confidence: 99%
“…Finally, with regard to cognitive training, developed under the hypothesis "use-itor-lose-it" during recent decades, studies have focused on cognitive plasticity, which is operationalized as the extent to which an individual can improve his/her performance in a given cognitive task through training [24], based on evaluation and intervention studies with experimental methods (see Table 2). Although several systematic reviews have highlighted that cognitive interventions improved cognitive performance only in the domain trained but not in other domains (moderate-strength evidence) [180][181][182], and they are not generalized to everyday situations [183,184], other systematic reviews and metaanalyses have shown evidence for small but consistent effects of cognitive interventions in improving cognition in healthy populations of aging adults, and that the results can be generalized to other mental abilities on non-trained measures [180,[185][186][187]; in addition, continued plasticity until age 80 and above is possible [150,188]. Along these lines, an analysis based on data from four major longitudinal studies in cognitive activity predicting cognitive outcomes over up to 21 years found that a change in cognitive engagement was associated with change in cognitive performance, although baseline activity at an earlier age and engagement did not predict rates of decline later in life, suggesting that change in cognitive activity from one's previous level has at least a transitory association with cognitive performance measured at the same point in time [189].…”
Section: Cognitive and Physical Trainingmentioning
confidence: 99%
“…Therefore, not only is WM training is theoretically expected to provide benefits in the trained WM tasks (so-called specific training gains) but also to give improvements in such a core cognitive mechanism would also produce general effects in untrained cognitive abilities related to it (so-called transfer effects) (e.g., Borella et al, 2017b ). According to recent reviews and meta-analyses (i.e., Karbach and Verhaeghen, 2014 ; Teixeira-Santos et al, 2019 ; Hou et al, 2020 ), WM training for healthy older adults has been shown to provide large (Karbach and Verhaeghen, 2014 ; Teixeira-Santos et al, 2019 ) and endurable (Hou et al, 2020 ) training gains in tasks similar to those trained. However, less consistent conclusions have been reported regarding the generalizability of WM training benefits: improvements to untrained tasks, i.e., transfer effects, usually are weaker than training gains are (Karbach and Verhaeghen, 2014 ), with mixed and less endurable effects (Teixeira-Santos et al, 2019 ; Hou et al, 2020 ), although some exceptions have been found (e.g., see Borella et al, 2017b , 2019a ).…”
Section: Introductionmentioning
confidence: 99%
“…According to recent reviews and meta-analyses (i.e., Karbach and Verhaeghen, 2014 ; Teixeira-Santos et al, 2019 ; Hou et al, 2020 ), WM training for healthy older adults has been shown to provide large (Karbach and Verhaeghen, 2014 ; Teixeira-Santos et al, 2019 ) and endurable (Hou et al, 2020 ) training gains in tasks similar to those trained. However, less consistent conclusions have been reported regarding the generalizability of WM training benefits: improvements to untrained tasks, i.e., transfer effects, usually are weaker than training gains are (Karbach and Verhaeghen, 2014 ), with mixed and less endurable effects (Teixeira-Santos et al, 2019 ; Hou et al, 2020 ), although some exceptions have been found (e.g., see Borella et al, 2017b , 2019a ).…”
Section: Introductionmentioning
confidence: 99%